Die Gewinnung landwirtschaftlicher Nutzflächen in Ägypten: Gegenwärtige Situation, Probleme und Ergebnisse - Hetzel, Wolfgang (ERDKUNDE, 1959)
The growing pressure of population forces Egypt to use all possible means of increasing its farm land notwithstanding or even because of the plans for industrialisation. A large scale land reclamation depends on the building of the planned high dam at Assuan. In the meantime attempts are being made in a short-term land reclamation programme to use all available water resources (Nile, suitable drainage water, ground water) for increasing the irrigated areas. The reclamation activities took a new leap forward after the 1952 revolution. The areas of the short-term land reclamation programme are situated mainly both in the northern part of the Nile delta and in the western desert. Thus different problems have already risen because of the different physical bases. These problems are illustrated by the author for a number of such reclamation areas which he visited himself (Maryut Lake, Idku Lake, Liberation Province, Wadi Natrun, Qarun Lake and others). The agrarian development of these areas is also different but economic considerations and agrarian policy plays a role in that, too. The social structure and conditions of tenure are based on the same principles which also apply for the areas where the agricultural reform has been carried out. All these efforts to increase the extent of the agriculturally used land, even the major projects in connexion with the building of the Assuan High Dam, will not suffice to solve the economic and social problems of the country, however, as long as the pronounced population increase continues.